Синхронний каскадний двигун з суміщеними обмотками - Лущик, В.Д.; Іваненко, В.С.; Борзік, В.Л. (Електротехніка і електромеханіка, 2011)
A synchronous cascade engine with combined windings is considered. The results of experimental researches are resulted. Advantages of synchronous cascade engine with combined windings are grounded as compared to slow synchronous engines.